2019
DOI: 10.3389/fimmu.2019.00452
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cytokines to Tissue Damage During Human Respiratory Syncytial Virus Infection

Abstract: The human respiratory syncytial virus (hRSV) remains one of the leading pathogens causing acute respiratory tract infections (ARTIs) in children younger than 2 years old, worldwide. Hospitalizations during the winter season due to hRSV-induced bronchiolitis and pneumonia increase every year. Despite this, there are no available vaccines to mitigate the health and economic burden caused by hRSV infection. The pathology caused by hRSV induces significant damage to the pulmonary epithelium, due to an excessive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 175 publications
(261 reference statements)
1
49
0
4
Order By: Relevance
“…Therefore, the intervention of ephedra-bitter almond on SARS-CoV-2 infected cells may also be carried out through the PI3K-Akt pathway. The excessive inflammatory response in the process of pathogen infection is destructive to the host, and when the production of pro-inflammatory cytokines increases, it causes serious damage to the lungs [ 66 ]. A study showed that IL-17 produced during viral infection specially enhanced the pro-inflammatory response by directly cooperating with antiviral signaling [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intervention of ephedra-bitter almond on SARS-CoV-2 infected cells may also be carried out through the PI3K-Akt pathway. The excessive inflammatory response in the process of pathogen infection is destructive to the host, and when the production of pro-inflammatory cytokines increases, it causes serious damage to the lungs [ 66 ]. A study showed that IL-17 produced during viral infection specially enhanced the pro-inflammatory response by directly cooperating with antiviral signaling [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is known to be a potent cytokine that amplifies the immune response through the activation of cytokine cascades as well as activation of critical innate immune cells, such as ILC2s. 18,19,35,36 Therefore, we decided to investigate the impact of IL-1βinduced immune activation on type 2 immunity-associated RSV immunopathology. To study the role of IL-1β during RSV infection, a neonatal murine model was utilized to recapitulate responses in clinical disease in infants ( Figure S1A).…”
Section: Rsv Induces Pulmonary Il-1β Expression In Infants and Neonmentioning
confidence: 99%
“…The authors, however, did not observe a difference in viral load or increased IFN-β expression between wildtype and IDO KO mice and suggested that this mouse model does not reflect the human disease. Other studies with RSV patients did not report on IFN-β (which may not have been overexpressed), but observed enhanced expression of a wide array of cytokines and chemokines in the lower and upper respiratory tracts (see [ 38 ] for a review). Levels of IFN-β and IDO expression therefore need to be measured in COVID-19 patients.…”
Section: Additional Findings Of Relevance To the Immune Effects And Tmentioning
confidence: 99%